Global Health: Unlocking Nanocarriers for the Programmed Release of Antimalarial Drugs (Global Challenges 2/2017) - Bagheri, Amir Reza (Glob Chall, 2017)
Electrospun nonwovens loaded with the anti‐Malaria drug Artemisone could be utilized as most efficient carrier without direct patient contact by infusion systems. The electrospun nonwovens allow high loading of Artemisone and excellent mass transfer. Drug release rate and dose could be controlled by choice of infusion media and infusion rate. Details can be found in the article number 1600011 by Amir Reza Bagheri, Seema Agarwal, Jacob Golenser, and Andreas Greiner*. [Image: see text]